Feasibility to use whole-genome sequencing as a sole diagnostic method to detect genomic aberrations in pediatric B-cell acute lymphoblastic leukemia - Rezayee, Fatemah; Eisfeldt, Jesper; Skaftason, Aron; Öfverholm, Ingegerd; Sayyab, Shumaila; Syvänen, Ann Christine; Maqbool, Khurram; Lilljebjörn, Henrik; Johansson, Bertil; Olsson-Arvidsson, Linda; Pietras, Christina Orsmark; Staffas, Anna; et al. (Frontiers in Oncology, 2023)
The suitability of whole-genome sequencing (WGS) as the sole method to detect clinically relevant genomic aberrations in B-cell acute lymphoblastic leukemia (ALL) was investigated with the aim of replacing current diagnostic methods. For this purpose, we assessed the analytical performance of 150 bp paired-end WGS (90x leukemia/30x germline) using a set of 88 retrospective B-cell ALL samples selected to represent established ALL subgroups as well as ALL lacking stratifying markers by standard-of-care (SoC), the so-called B-other ALL. Both the analysis of paired leukemia/germline samples (L/N) (n=64) as well as leukemia-only (Lonly) (n=88) detected all types of aberrations mandatory in the current ALLtogether trial protocol, i.e., aneuploidies, structural variants, and focal copy-number aberrations. Moreover, comparison to SoC revealed 100% concordance and that all patients had been assigned to the correct genetic subgroup using both approaches. Notably, WGS could allocate 35 out of 39 Bother ALL samples to one of the emerging genetic subgroups considered in the most recent classifications of ALL. The filtration of the WGS findings with a short list of genes recurrently rearranged in ALL was instrumental to extract the clinically relevant information efficiently.Nonetheless, the detection of DUX4 rearrangements required an additional customized analysis, due to multiple copies of this gene embedded in the highly repetitive D4Z4 region. We further investigated the impact of high (90x; n=58) vs low (30x; n=30) coverage on the diagnostic yield and observed an equally perfect concordance with SoC; low coverage detected all relevant lesions. We conclude that the diagnostic performance of WGS as the standalone method was remarkable and allowed detection of all clinically relevant genomic events in the diagnostic setting of B-cell ALL.